Mixed Type Basal Cell Carcinoma Treated with Excision and Defect Closure Using Advancement Flap: A Case Report - Darmaputra, I Gusti Nyoman; Ketut Kwartantaya Winaya; Adelia Suryani; Herman Saputra; Putu Setiani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Basal cell carcinoma (BCC) is a localized malignant tumor in the basal layer of the epidermis thought to be the result of prolonged sun exposure and associated with gene mutations in most cases. Although rarely metastazises, BCC can cause high levels of morbidity due to its locally destructive nature. There are several modalities for managing BCC, and the defect caused by the lesion can reconstructed by local flap. Case presentation: We present a 55-year-old woman with a chief complaint of a blackish lump on the left maxillary region, growing bigger, and frequent episodes of bleeding. The lesion was excised and followed by histopathological examination, which revealed mixed subtype BCC. Closure of the defect with an advancement flap was performed with favorable results. Conclusion: Surgical excision is the best option for managing BCC, while a skin flap is preferred to close defects for lesions on the cheek.